2015
DOI: 10.1111/chd.12293
|View full text |Cite
|
Sign up to set email alerts
|

Fractures Related to Metabolic Bone Disease in Children with Congenital Heart Disease

Abstract: Critically ill CHD patients are at risk for fractures. They represent a complex group who frequently has hyperparathyroidism and decreased calcitriol levels, and each may predispose to fractures. FBPs consisting of identification and careful patient handling should be considered in at-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…In a small and limited retrospective study, Cheng et al reviewed the medical records of children admitted to a cardiac intensive care unit to characterize a cohort of patients with congenital heart defects and fractures, and the researchers described a fragile bone protocol to reduce fractures. 31 The study found 2 fracture cases per 1000 admissions (15 patients with 23 fractures), with 87% sustaining fractures after surgery (mean age, 6 months; range, 2-23 months). Alterations to the homeostatic balance of parathyroid hormone and vitamin D were commonly seen in patients: 77% of patients had hyperparathyroidism; 40% had hypovitaminosis D (despite being supplemented to 400 U/d); and 33% had both.…”
Section: Vitamin D and Calciummentioning
confidence: 90%
See 4 more Smart Citations
“…In a small and limited retrospective study, Cheng et al reviewed the medical records of children admitted to a cardiac intensive care unit to characterize a cohort of patients with congenital heart defects and fractures, and the researchers described a fragile bone protocol to reduce fractures. 31 The study found 2 fracture cases per 1000 admissions (15 patients with 23 fractures), with 87% sustaining fractures after surgery (mean age, 6 months; range, 2-23 months). Alterations to the homeostatic balance of parathyroid hormone and vitamin D were commonly seen in patients: 77% of patients had hyperparathyroidism; 40% had hypovitaminosis D (despite being supplemented to 400 U/d); and 33% had both.…”
Section: Vitamin D and Calciummentioning
confidence: 90%
“…Critically ill patients with HF may be at risk for developing metabolic bone disease and subsequent fractures. They have cumulative exposures to several risk factors, such as vitamin D deficiency, renal insufficiency, poor nutrition, immobilization, and effects of certain medications (eg, diuretics) . Additionally, they may have hyperparathyroidism and decreased calcitrol levels.…”
Section: Macronutrients and Micronutrients In Hfmentioning
confidence: 99%
See 3 more Smart Citations